2006
DOI: 10.1007/s11422-006-9013-1
|View full text |Cite
|
Sign up to set email alerts
|

Using Sociocultural Theory to Understand the Relationship between Teacher Change and a Science-based Professional Education Program

Abstract: This paper focuses on a model of teacher change based on a study of a science discipline-based professional education program and on an understanding of teacher change in terms of an agency|structure dialectic. Professional education programs should expand teachers' capacity to act in a range of fields. Conducted over one year, this study used sociocultural theory to examine the role of cultural schema and resources in the enactment of new pedagogical structures by two teachers who demonstrated widely variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…This entails intentionally interacting with others as a resource for learning and acting as a support for them (Edwards, 2005;Pyhältö & Keskinen, 2012). Teachers' professional agency refers also to teacher's ability to act in new and creative ways, and even to resist external norms and regulations when they are understood to contrast or conflict with professionally justifiable action (Dovemark, 2010;Florio-Ruane, 2002;Lasky, 2005;Milne, Scantlebury, & Otieno, 2006).…”
Section: Teachers' Professional Agency -What Is It All About?mentioning
confidence: 99%
“…This entails intentionally interacting with others as a resource for learning and acting as a support for them (Edwards, 2005;Pyhältö & Keskinen, 2012). Teachers' professional agency refers also to teacher's ability to act in new and creative ways, and even to resist external norms and regulations when they are understood to contrast or conflict with professionally justifiable action (Dovemark, 2010;Florio-Ruane, 2002;Lasky, 2005;Milne, Scantlebury, & Otieno, 2006).…”
Section: Teachers' Professional Agency -What Is It All About?mentioning
confidence: 99%
“…There are five subscales ("What I do," "What my teacher does," and "At least one adult in home", "What my friends do in science and the "My attitude towards science") using a Likert-type scale, ranging from Almost Never (1) to Very Often (5), for the four subscales (student classroom behaviors, teacher classroom behaviors, peer involvement in science, and adulf parental support of student's science studies). Items assessing student attitudes toward science use a different five-point Likert scale, with values ranging from Strongly Disagree (I) to Strongly Agree (5). Using the Rasch model, the raw scores are converted to a hnear scale that ranges from 0-100.…”
Section: Resultsmentioning
confidence: 99%
“…Professional development programs aimed at improving teachers' content knowledge and promoting inquiry-based teaching are challenged with providing teachers content knowledge and using pedagogical approaches that model standards based instruction [5]. Studies have shown that student achievement is positively correlated to teacher content knowledge.…”
Section: Importance Of Teacher Professional Development On Student Acmentioning
confidence: 99%
“…It suggests that she has no intention to change. Capacity for agency involves forming intentions, setting goals and acting creatively (Milne et al 2006 ). During the observation phase, Jenny did not exhibit any agency to act in relation to the reform, as she did not pay attention to the reform agenda.…”
Section: Excerpt 544mentioning
confidence: 99%